PERSEPSI MAHASISWA TERHADAP PENERAPAN INTERPROFESSIONAL EDUCATION DALAM PROGRAM FOME II FAKULTAS KEDOKTERAN UNIVERSITAS ANDALAS 2021-2022 - Rahman, Fikri; Yetti, Husna; Elliyanti, Aisyah (SINERGI : Jurnal Riset Ilmiah, 2025)
Collaboration between health professionals was needed to improve health services. The collaboration can be applied to the education system through the Interprofessional Education (IPE) concept. The purpose of this study was to examine students’ perception of IPE in the Family Oriented Medical Education (FOME) II program. This research is a descriptive study with a cross-sectional design. The research samples were 162 Medical Faculty Universitas Andalas students who took part in the FOME II program in the 2021-2022 academic year. FOME II is a learning activities created by FK Unand with the aim of producing competent health workers with a family approach. There were 142 medical study program students and 20 undergraduate midwifery study program students. Study data was collected by using the Interdisciplinary Education Perception Scale (IEPS) questionnaire.  The vast majority of students(153 students,94.4%) had a good perception on IPE with the evidence of working together’s component having the highest percentage (90.7%) and needing to work together’s component had the lowest percentage (59.9%). Medical Study Program students have the highest percentage of the application of IPE perception (95.7%) while midwifery study program students have the lowest percentage of the application of IPE perception (85%).  Most of FK Unand students’ perceptions of IPE are in the good category. However, the aspect of the need to cooperate is still lacking so this needs to be considered and improved